PERHITUNGAN PATHLOSS TEKNOLOGI 4G LONG TERM EVOLUTION (LTE) - Maria Ulfah (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2016)
Wave propagation through an air transmission medium is important for the smooth mobile communications, because the signal is distributed by the air transmission medium to be received by the recipient is affected by the contours of the earth , media reflection , the obstacle and the distance and the possibilities that can not be predicted appearance and inhibit the signal transmission process is in progress. Important to take into account pathloss signals that occur along the transmission line , because it affects the quality of the signal to be received . In determining the loss signal propagation model is used in accordance with the COST 231 for 1800 MHz 4G LTE frequency.In this study calculated pathloss signal 4G LTE with distance variation antena transmitter (E node B) to the receiver (mobile station ) is 1 km, 5 km, 10 km, 15 km, 20 km, with a height of antena transmitter 24 meter . From the results of the calculation, the greater the distance between the transmitter antena towards the receiver pathloss value is the greater of 138.8853 Db to 175.4915 dB. Meanwhile, if the receiver antena height is enlarged to the distance d between the eNodeB with MS remain the pathloss value to decrease. The greater the value of pathloss the received signal quality will decline and otherwise